Effect of Demineralized Bone Matrix, Bone Marrow Mesenchymal Stromal Cells, and Platelet-Rich Plasma on Bone Tunnel Healing After Anterior Cruciate Ligament Reconstruction: A Comparative Micro-Computed Tomography Study in a Tendon Allograft Sheep Model. Issue 9 (21st September 2021) - Hexter, Adam T.; Karali, Aikaterina; Kao, Alex; Tozzi, Gianluca; Heidari, Nima; Petrie, Aviva; Boyd, Ashleigh; Kalaskar, Deepak M.; Pendegrass, Catherine; Rodeo, Scott; Haddad, Fares; Blunn, Gordon
Background: The effect of demineralized bone matrix (DBM), bone marrow–derived mesenchymal stromal cells (BMSCs), and platelet-rich plasma (PRP) on bone tunnel healing in anterior cruciate ligament reconstruction (ACLR) has not been comparatively assessed. Hypothesis: These orthobiologics would reduce tunnel widening, and the effects on tunnel diameter would be correlated with tunnel wall sclerosis. Study Design: Controlled laboratory study. Methods: A total of 20 sheep underwent unilateral ACLR using tendon allograft and outside-in interference screw fixation. The animals were randomized into 4 groups (n = 5 per group): Group 1 received 4mL of DBM paste, group 2 received 10 million BMSCs in fibrin sealant, group 3 received 12 mL of activated leukocyte-poor platelet-rich plasma, and group 4 (control) received no treatment. The sheep were euthanized after 12 weeks, and micro-computed tomography scans were performed. The femoral and tibial tunnels were divided into thirds (aperture, midportion, and exit), and the trabecular bone structure, bone mineral density (BMD), and tunnel diameter were measured. Tunnel sclerosis was defined by a higher bone volume in a 250-µm volume of interest compared with a 4-mm volume of interest surrounding the tunnel. Results: Compared with the controls, the DBM group had a significantly higher bone volume fraction (bone volume/total volume [BV/TV]) (52.7% vs 31.8%; P = .020) and BMD (0.55 vs 0.47 g/cm 3 ; P = .008) at the femoral aperture and significantly higher BV/TV at femoral midportion (44.2% vs 32.9%; P = .038). There were no significant differences between the PRP and BMSC groups versus controls in terms of trabecular bone analysis or BMD. In the controls, widening at the femoral tunnel aperture was significantly greater than at the midportion (46.7 vs 41.7 mm 2 ; P = .034). Sclerosis of the tunnel was common and most often seen at the femoral aperture. In the midportion of the femoral tunnel, BV/TV ( r = 0.52; P = .019) and trabecular number ( r S = 0.50; P = .024) were positively correlated with tunnel widening. Conclusion: Only DBM led to a significant increase in bone volume, which was seen in the femoral tunnel aperture and midportion. No treatment significantly reduced bone tunnel widening. Tunnel sclerosis in the femoral tunnel midportion was correlated significantly with tunnel widening. Clinical Relevance: DBM might have potential clinical use to enhance healing in the femoral tunnel after ACLR.